Preparation method and application of two-dimensional ultrathin porous nitrogen-doped carbon composite material
Ultrathin porous nitrogen-doped carbon nanosheets loaded with metal single atoms and nanoparticles were prepared by metal salt anion-mediated method, which solved the problems of impedance mismatch in highly graphitized carbon materials and the complexity of traditional porous structures. This method achieved efficient electromagnetic wave absorption, improved the synergy between dielectric loss and magnetic loss, and was simple and environmentally friendly.
Patent Information
- Application Number
- CN202511630028.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-08
- Publication Date
- 2026-02-10
AI Technical Summary
Existing carbon materials with high graphitization levels exhibit excessively high electrical conductivity, leading to impedance mismatch and severe reflection of incident electromagnetic waves. Traditional porous structure preparation methods are complex and energy-intensive, making it difficult to introduce controllable multi-scale porous structures into ultrathin two-dimensional materials. Furthermore, the dielectric and magnetic losses of two-dimensional electromagnetic wave absorbing materials are not sufficiently coordinated, limiting their absorption performance.
An anion-mediated method using metal salts was employed to prepare ultrathin porous nitrogen-doped carbon nanosheets loaded with metal single atoms and nanoparticles by mixing dopamine hydrochloride with metal salts and carbonizing them in the presence of an oxidant. Multi-scale porous structures were formed by utilizing the local explosion effect and etching effect induced by nitrate decomposition.
The porous structure was controllable and tunable, impedance matching was optimized, electromagnetic wave absorption capacity was improved, and electromagnetic loss mechanism was enhanced. The material achieved an absorption bandwidth of 10.1 GHz and an absorption intensity of -119.1 dB at a thickness of 2.1 mm. The preparation method is simple and environmentally friendly.
Smart Images

Figure CN121493930A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electromagnetic wave absorbing materials, and particularly relates to a method for preparing and applying a two-dimensional ultrathin porous nitrogen-doped carbon composite material. Background Technology
[0002] In the booming 5G / 6G era of advanced electronic devices and wireless communications, electromagnetic wave absorbing materials are considered one of the most important solutions to address the increasingly severe electromagnetic pollution and effectively maintain information security. To date, two-dimensional materials with large specific surface area, tunable layered structures, and high chemical stability have demonstrated valuable advantages in the design of high-performance electromagnetic wave absorbing systems. The nanoscale thickness of two-dimensional nanosheets can effectively avoid the skin effect at gigahertz frequencies, while the dispersed multilayer structure can effectively extend the transmission path of electromagnetic waves through multiple scattering / reflection, thereby increasing the energy dissipation of incident electromagnetic waves. Furthermore, two-dimensional materials can serve as substrates for magnetic components, enabling the effective dispersion of magnetic nanoparticles and laying the foundation for achieving stable magnetic responses.
[0003] Nitrogen-doped carbon nanosheets have recently become a research hotspot in two-dimensional electromagnetic wave absorbing materials. The doped N atoms can anchor metal atoms through metal-N bonds, thereby altering the electronic structure of the carbon matrix. dp orbital hybridization between the metal atoms and the N / C species leads to space charge separation and local electron migration, and the induced relaxation effect can significantly enhance polarization loss under alternating electromagnetic fields.
[0004] However, the pyrolysis process that transforms the corresponding precursor into nanosheets typically requires high carbonization temperatures, leading to a high degree of graphitization of the carbon support. While a well-crystallized carbon support can impart higher electrical conductivity to the system, thereby improving its conductivity loss capability, it also results in severe impedance mismatch. In this case, a significant amount of incident electromagnetic waves will be reflected at the absorber-air interface, hindering the improvement of the final microwave absorption performance. Therefore, effectively mitigating the contradiction between high conductivity and low interface reflection is a pressing issue that needs to be addressed.
[0005] One possible solution is to introduce abundant porous structures into the system without disrupting the continuity of the carbon matrix. Introducing porous structures into two-dimensional sheets can be achieved through polystyrene or silica microsphere templates or molten salt methods, where the pore size is determined by the size of the sacrificial template. However, these traditional pore-forming methods are energy-intensive, time-consuming, and require the introduction of additional components. More importantly, introducing a large number of multi-scale pores into ultrathin two-dimensional materials is quite difficult, hindering further improvements in the electromagnetic performance of two-dimensional electromagnetic wave absorbing systems. Therefore, there remains an urgent need to explore flexible and efficient methods to prepare nanosheet materials with controllable porosity structures. Summary of the Invention
[0006] The technical problems solved by this invention are: 1. Existing carbon materials have excessively high electrical conductivity at high graphitization levels, resulting in impedance mismatch and severe reflection of incident electromagnetic waves; 2. Traditional porous structure preparation methods are complex and energy-intensive, making it difficult to introduce controllable multi-scale porous structures in ultrathin two-dimensional materials; 3. The dielectric loss and magnetic loss of two-dimensional electromagnetic wave absorbing materials are not sufficiently synergistic, limiting their absorption performance.
[0007] In view of the technical problems existing in the prior art, the present invention designs a method for preparing two-dimensional ultrathin porous nitrogen-doped carbon composite material and its application.
[0008] It should be noted that, in this invention, unless otherwise specified, the specific meaning of "comprising" in relation to composition definition and description includes both open-ended meanings such as "comprising," "including," etc., and closed-ended meanings such as "composed of," etc., and similar meanings.
[0009] To solve the aforementioned technical problems, the present invention adopts the following solution: [The first technical solution] A method for preparing a two-dimensional ultrathin porous nitrogen-doped carbon composite material includes the following steps: Step 1: Mix dopamine hydrochloride (DA) and metal salt at a mass ratio of 1:0.5-7 and grind thoroughly to obtain a ground mixture; Step 2: Add oxidant and deionized water to the grinding mixture from Step 1, continue grinding and then dry to obtain the reaction precursor; Step 3: The dried reaction precursor is carbonized under an inert atmosphere to obtain the composite material; Wherein, the metal salt is a metal nitrate; The metal in question is one of iron, cobalt, nickel, manganese, silver, and copper.
[0010] Further, the oxidant in step 2 is a hydrogen peroxide solution, and the amount of hydrogen peroxide solution added is 0.1-2 mL per gram of dopamine hydrochloride.
[0011] Further, the carbonization process described in step 3 is as follows: first, the temperature is increased to 200-300℃ at a rate of 1-5℃ / min, and then increased to 600-1000℃ at a rate of 3-10℃ / min and held for 0.5-3 hours.
[0012] Furthermore, the carbonization process described in step 3 is carried out under an argon atmosphere with a gas flow rate of 50-500 sccm.
[0013] This invention designs a metal salt anion-mediated method and successfully prepares ultrathin porous nitrogen-doped carbon nanosheets loaded with metal single atoms and metal nanoparticles.
[0014] By changing the type of metal salt anion, a controllable switch between non-porous and porous structures can be achieved.
[0015] In this invention, the mechanism for preparing the composite material is as follows: After a vigorous grinding process, metal ions are firmly anchored in dopamine through chelation with catechol groups. The inherent oxidizing power of the metal ions induces the self-polymerization of dopamine, forming a layered metal-PDA mixture. During the subsequent carbonization process, the thermal motion of metal atoms is effectively suppressed, thus avoiding the tendency for severe aggregation at high temperatures.
[0016] Taking the reaction of metallic iron as an example, the final product inherits the layered morphology of the precursor, exhibiting ultrathin sheet-like characteristics, and its surface is simultaneously loaded with Fe single atoms and nanoparticles. The preparation reaction process is as follows: Figure 1 As shown.
[0017] In this invention, the selection of nitrate as the metal anion is of unique significance: The formation of porous structures is closely related to the pyrolysis properties of nitrate. During the accelerated stage of the carbonization process, the localized explosion effect triggered by nitrate decomposition disrupts the structural integrity of the layered PDA precursor surface, laying the foundation for the combination of multi-scale pores.
[0018] On the other hand, the etching effect generated by nitric acid gas also contributes to the evolution of porous properties. Therefore, a rich multi-scale porous structure was successfully introduced into the nanosheets.
[0019] [Second Technical Solution] The present invention also discloses a two-dimensional ultrathin porous nitrogen-doped carbon composite material, which is prepared by the above-described preparation method.
[0020] Furthermore, the two-dimensional ultrathin porous nitrogen-doped carbon composite material has a sheet-like porous structure and is loaded with metal single atoms and metal nanoparticles; wherein the metal is one of iron, cobalt, nickel, manganese, silver and copper.
[0021] Furthermore, the two-dimensional ultrathin porous nitrogen-doped carbon composite material has a specific surface area of 100-1000 m² / g and an average pore size of 10-50 nm.
[0022] [The third technical solution] The present invention also discloses the application of the above-mentioned two-dimensional ultrathin porous nitrogen-doped carbon composite material in electromagnetic wave absorption, electromagnetic shielding, electromagnetic compatibility, medical radiation protection or radar stealth materials.
[0023] Regarding its specific application methods, the following examples can be provided: Firstly, electromagnetic compatibility Electromagnetic compatibility (EMC) surface mount components are key devices for solving electromagnetic interference (EMI) and signal integrity problems in electronic devices, and can be used to suppress broadband electromagnetic radiation. Specific applications include: RF modules in communication equipment, where absorbing patches reduce inter-antenna coupling and match network impedance tuning; and automotive electronics, where absorbing patches suppress high-frequency bus interference.
[0024] Secondly, medical radiation protection Specific applications include: wave-absorbing coatings on computer room floors, which absorb electromagnetic waves through the synergistic effect of dielectric and magnetic loss, reducing electromagnetic leakage when equipment is moved; radiation protection clothing, which is combined with biodegradable polymers to make protective pads or work clothes for pregnant women, suppressing low-frequency radiation; and wave-absorbing liners for radioactive waste storage containers, which, combined with lead shielding layers, shield strong radioactive sources.
[0025] Third, radar stealth materials Specific application scenarios include: stealth coatings for aircraft, which use radar-absorbing coatings to cover strong scattering parts such as the fuselage, wings, and leading edges to suppress X-band radar reflection; and stealth coatings for ships, which use radar-absorbing coatings to cover the hull and, combined with a tilted mast design, reduce S-band radar reflection signals.
[0026] This invention provides a method for preparing two-dimensional ultrathin porous nitrogen-doped carbon composite materials and their applications, which have the following beneficial effects: 1. The preparation method of the present invention can effectively control the porous structure, and the etching effect generated by nitric acid gas also helps the evolution of porous properties, realizing a controllable switch from non-porous to porous.
[0027] 2. The material prepared by the method of the present invention has optimized impedance matching, and the porous structure reduces the dielectric constant and enhances the electromagnetic wave absorption capability.
[0028] 3. The material of the present invention has an enhanced electromagnetic loss mechanism: electron migration between metal single atoms and metal nanoparticles enhances dielectric polarization, and metal nanoparticles provide magnetic loss.
[0029] 4. The material in this invention has excellent absorption performance: at a thickness of 2.1 mm, the FeNC-NO3 absorption bandwidth reaches 10.1 GHz and the absorption intensity reaches -119.1 dB; 5. The preparation method of the present invention is simple, green, and requires no additional template, making it suitable for large-scale preparation. Attached Figure Description
[0030] Figure 1 Schematic diagram of the synthesis process of two-dimensional ultrathin porous nitrogen-doped carbon nanosheets; Figure 2SEM and TEM images of FeNC-NO3 prepared in Example 1 of this invention: a) SEM image, b) TEM image, c) high-resolution image, d) corresponding elemental distribution map; Figure 3 XRD pattern of FeNC-NO3 prepared in Example 1 of this invention; Figure 4 The AC-STEM image and synchrotron radiation spectrum of FeNC-NO3 prepared in Example 1 of this invention and their fitting diagram, a, b) HAADF-STEM image of FeNC-NO3 nanosheets and corresponding electron energy loss spectrum, c) high-resolution deconvolution XPS spectrum of Fe element of FeNC nanosheets, df) synchrotron radiation spectrum of FeNC-NO3 nanosheets, and g1) corresponding wavelet transform spectrum; Figure 5 : A schematic diagram of the nitrogen adsorption-desorption curve, specific surface area, and average pore size of FeNC-NO3 in Example 1 of this invention; Figure 6 Electromagnetic wave absorption performance diagram of FeNC-NO3 prepared in Example 1 of this invention; Figure 7 SEM images of CoNC-NO3 and NiNC-NO3 materials prepared in Examples 4-5 of this invention. Detailed Implementation
[0031] The present invention will be further described below with reference to specific embodiments and accompanying drawings: It should be noted that the raw materials used in the embodiments of the present invention are as follows: Dopamine hydrochloride (DA, 98%), ferric nitrate nonahydrate (Fe(NO3)3·9H2O, 98.5%), ferric acetate hydrate (C4H7FeO5·nH2O), ferric chloride hexahydrate (FeCl3·6H2O, 99%), ferric sulfate pentahydrate (Fe2H 10 O 17 S3 (97%), cobalt nitrate hexahydrate (Co(NO3)2•6H2O, 99%) were purchased from Maclin. Nickel nitrate hexahydrate (Ni(NO3)2•6H2O, 99%), manganese nitrate tetrahydrate (Mn(NO3)2•4H2O), silver nitrate (AgNO3), and copper nitrate trihydrate (Cu(NO3)2·3H2O) were purchased from Aladdin. Hydrogen peroxide solution (H2O2, 30wt%) was purchased from Maokang Biotechnology Co., Ltd. All chemicals were used directly without further purification. Example 1
[0032] Step 1: Mix 0.6g of dopamine hydrochloride and 1.8g of ferric nitrate nonahydrate together and grind thoroughly for 30 minutes.
[0033] Step 2: Add 0.3 mL of hydrogen peroxide solution and 5 mL of deionized water to the mixture and continue grinding for 30 minutes. Then transfer the obtained mixture to a vacuum drying oven and keep it at 70°C overnight.
[0034] Step 3: After complete drying, the mixture is ground into powder and transferred to a vacuum tube furnace for carbonization at a flow rate of 500 sccm under an Ar atmosphere. The heating process is divided into two parts: first, heating to 250°C at a heating rate of 5°C / min, and then heating to 750°C at a rate of 8°C / min and holding for 1 hour. The black powder product is designated as FeNC-NO3. Example 2
[0035] FeNC-NO3 with a small and a large number of multi-scale pores on a carbon matrix was synthesized using a similar process described above.
[0036] Step 1: Mix 1.8g of dopamine hydrochloride and 0.9g of ferric nitrate nonahydrate together and grind for 20 minutes.
[0037] Step 2: Add 0.2 mL of hydrogen peroxide solution and 1.0 mL of deionized water to the mixture and continue grinding for 20 minutes. Then transfer the obtained mixture to a vacuum drying oven and keep it at 80°C overnight.
[0038] Step 3: After complete drying, the mixture is ground into powder and transferred to a vacuum tube furnace for carbonization at a flow rate of 50 sccm under an Ar atmosphere. The heating process is divided into two parts: first, heating to 200°C at a heating rate of 3°C / min, and then heating to 600°C at a rate of 3°C / min and holding for 0.5 hours. The black powder product is designated as FeNC-NO3. Example 3
[0039] FeNC-NO3 with a small and a large number of multi-scale pores on a carbon matrix was synthesized using a similar process described above.
[0040] Step 1: Mix 0.4g of dopamine hydrochloride and 2.8g of ferric nitrate nonahydrate together and grind for 25 minutes.
[0041] Step 2: Add 0.25 mL of hydrogen peroxide solution and 3 mL of deionized water to the mixture and continue grinding for 25 minutes. Then transfer the obtained mixture to a vacuum drying oven and keep it at 90°C overnight.
[0042] Step 3: After complete drying, the mixture is ground into powder and transferred to a vacuum tube furnace for carbonization at a flow rate of 250 sccm under an Ar atmosphere. The heating process is divided into two parts: first, heating to 300°C at a heating rate of 4°C / min, and then heating to 1000°C at a rate of 10°C / min and holding for 3 hours. The black powder product is designated as FeNC-NO3.
[0043] The products in Examples 2 and 3 exhibit a sheet-like thin-layer structure with numerous multi-scale porous defects on the surface. The prepared FeNC-NO3 nanosheets simultaneously support Fe single atoms and nanoparticles. Their specific surface area is greater than 100 m². 2 g -1 It has an average pore size greater than 10 nm, a maximum absorption intensity greater than -80 dB, and an effective absorption bandwidth greater than 7.0 GHz with a 2 mm matching thickness. Example 4
[0044] The preparation method of this embodiment is basically the same as that of Example 1, except that cobalt nitrate hexahydrate is used instead of ferric nitrate nonahydrate, and the corresponding product is named CoNC-NO3.
[0045] CoNC-NO3 possesses a layered porous structure with a specific surface area of 372.78 m². 2 g -1 It has an average pore size of 22.29 nm, a maximum absorption intensity of -122.2 dB, and an effective absorption bandwidth of 6.7 GHz with a matching thickness of 2.0 mm. Example 5
[0046] The preparation method in this embodiment is basically the same as that in Example 1, except that nickel nitrate hexahydrate is used instead of ferric nitrate nonahydrate, and the corresponding product is named NiNC-NO3.
[0047] NiNC-NO3 possesses a layered porous structure with a specific surface area of 254.15 m². 2 g -1 The average aperture is 10.04 nm, the maximum absorption intensity is -61.2 dB, and the effective absorption bandwidth is 10.7 GHz with a matching thickness of 2.3 mm.
[0048] Figure 7 These are SEM images of the CoNC-NO3 and NiNC-NO3 materials prepared in Examples 4-5 of this invention; from Figure 7 As can be seen, both CoNC-NO3 and NiNC-NO3 exhibit a sheet-like thin-layer structure with numerous multi-scale pore defects on their surfaces, and the surface pore structure has multi-scale characteristics ranging from micropores to mesopores. Example 6
[0049] The preparation method of this embodiment is basically the same as that of Example 1, except that manganese nitrate tetrahydrate is used instead of ferric nitrate nonahydrate, and the corresponding product is named MnNC-NO3. Example 7
[0050] The preparation method in this embodiment is basically the same as that in Example 1, except that silver nitrate is used instead of ferric nitrate nonahydrate, and the corresponding product is named AgNC-NO3. Example 8
[0051] The preparation method of this embodiment is basically the same as that of Example 1, except that copper nitrate trihydrate is used instead of ferric nitrate nonahydrate, and the corresponding product is named CuNC-NO3.
[0052] The composite materials MnNC-NO3, AgNC-NO3, and CuNC-NO3 prepared in Examples 6-8 all exhibit a lamellar thin-layer structure with numerous multi-scale pore defects on the surface, displaying multi-scale characteristics ranging from micropores to mesopores. The maximum absorption intensity is higher than -60 dB, and the effective absorption bandwidth is greater than 6.0 GHz at a 2.0 mm matching thickness.
[0053] The material prepared in Example 1 of the present invention was characterized and described accordingly: Firstly, regarding microscopic morphology Figure 2 These are SEM and TEM images of the product from Embodiment 1 of the present invention; from Figure 2 As can be seen from this, its microscopic characteristics are: SEM images show that FeNC-NO3 has a sheet-like thin-layer structure with a large number of multi-scale pore defects on its surface.
[0054] TEM images further reveal that the nanosheets possess a graphene-like morphology, with a multi-scale surface pore structure exhibiting characteristics ranging from micropores to mesopores. They are also loaded with Fe nanoparticles, approximately 80 nm in size.
[0055] Secondly, regarding crystal structure Figure 3 The image shows the XRD pattern of FeNC-NO3 prepared in Example 1 of this invention. from Figure 3 It can be seen that the different diffraction peaks at 44.7° and 65.0° can be attributed to the (110) and (200) crystal planes of cubic Fe (PDF#06-0696), indicating that well-crystallized Fe nanoparticles were formed on FeNC nanosheets.
[0056] It should be noted that the accompanying drawings of some embodiments of the present invention include comparative descriptions of the performance of other FeNC absorbents. Other methods for preparing FeNC nanosheets are described below: The preparation method in this embodiment is basically the same as that in Example 1, except that ferric sulfate pentahydrate is used instead of ferric nitrate nonahydrate, and the corresponding product is named FeNC-SO4; ferric chloride hexahydrate is used instead of ferric nitrate nonahydrate, and the corresponding product is named FeNC-Cl; and ferric acetate hydrate is used instead of ferric nitrate nonahydrate, and the corresponding product is named FeNC-OAc.
[0057] Thirdly, regarding the loaded iron single atoms Figure 4 The images show the AC-STEM image and synchrotron radiation spectrum of the product FeNC-NO3 in Example 1 of this invention; a, b) HAADF-STEM images and corresponding electron energy loss spectra of FeNC-NO3 nanosheets; c) high-resolution deconvolution XPS image of Fe element in FeNC nanosheets; df) synchrotron radiation spectrum of FeNC-NO3 nanosheets; and g1) corresponding wavelet transform spectrum.
[0058] from Figure 4 It can be seen that, due to the difference in electron energy density between the metal and carbon atoms, Fe single atoms can be detected as isolated bright spots on the carbon substrate, indicating a uniform loading of Fe single atoms on the carbon substrate. The electron energy loss spectrum of the corresponding labeled region further confirms the distribution of Fe atoms. Simultaneously, fitting analysis of the K-edge synchrotron radiation spectrum of the Fe element in the sample shows that FeNC-NO3 simultaneously possesses Fe-Fe coordination and Fe-N coordination. These results verify that the prepared FeNC-NO3 nanosheets simultaneously load Fe single atoms and nanoparticles.
[0059] Fourth, regarding nitrogen adsorption-desorption measurement Figure 5 This is a schematic diagram of the nitrogen adsorption-desorption curve, specific surface area, and average pore size of FeNC-NO3 in Example 1 of the present invention. from Figure 5 It can be seen that FeNC-NO3 nanosheets have a diameter of 163.03 μm. 2 g -1 Its large specific surface area and large average pore size of 13.13 nm, compared with Figure 2 The observed porous structure matches the pattern. The formation of the porous structure is closely related to the pyrolysis properties of nitrate.
[0060] During the accelerated phase of the carbonization process, the localized explosion effect triggered by nitrate decomposition disrupts the structural integrity of the layered PDA precursor surface, laying the foundation for the integration of multi-scale pores. On the other hand, the etching effect generated by nitric acid gas also contributes to the evolution of porous properties. Therefore, a rich multi-scale porous structure was successfully introduced into FeNC-NO3 nanosheets.
[0061] Fifth, regarding electromagnetic wave absorption performance Figure 6 The electromagnetic wave absorption performance diagram of FeNC-NO3 prepared in Example 1 of this invention is shown. from Figure 6 It can be seen that the FeNC-NO3 sample not only maintains an excellent effective absorption bandwidth but also exhibits a significantly enhanced maximum absorption intensity. With a matched thickness of 2.1 mm, its effective absorption bandwidth reaches 10.1 GHz, while the maximum absorption intensity reaches -119.1 dB. It can be reasonably inferred that the improved absorption intensity of the FeNC-NO3 sample is mainly due to the introduction of multi-scale porous defects. Simultaneously, the nitrate-mediated porous structure also promotes the shift of the maximum reflection loss value from high frequencies to mid frequencies, expanding the practical application prospects of FeNC composite materials.
[0062] The present invention has been described above by way of example with reference to the embodiments and accompanying drawings. Obviously, the implementation of the present invention is not limited to the above-described manner. Any improvements made by adopting the inventive concept and technical solution of the present invention, or the direct application of the inventive concept and technical solution of the present invention to other occasions without modification, are all within the protection scope of the present invention.
Claims
1. A method for preparing a two-dimensional ultrathin porous nitrogen-doped carbon composite material, characterized in that, Includes the following steps: Step 1: Mix dopamine hydrochloride (DA) and metal salt at a mass ratio of 1:0.5-7 and grind thoroughly to obtain a ground mixture; Step 2: Add oxidant and deionized water to the grinding mixture from Step 1, continue grinding and then dry to obtain the reaction precursor; Step 3: The dried reaction precursor is carbonized under an inert atmosphere to obtain the composite material; Wherein, the metal salt is a metal nitrate; The metal in question is one of iron, cobalt, nickel, manganese, silver, and copper.
2. The method for preparing the two-dimensional ultrathin porous nitrogen-doped carbon composite material according to claim 1, characterized in that: The oxidant in step 2 is a hydrogen peroxide solution, and the amount of hydrogen peroxide solution added is 0.1-2 mL per gram of dopamine hydrochloride.
3. The method for preparing two-dimensional ultrathin porous nitrogen-doped carbon composite material according to claim 1, characterized in that: The carbonization process described in step 3 is as follows: first, the temperature is increased to 200-300℃ at a rate of 1-5℃ / min, and then the temperature is increased to 600-1000℃ at a rate of 3-10℃ / min and held for 0.5-3 hours.
4. The method for preparing the two-dimensional ultrathin porous nitrogen-doped carbon composite material according to claim 1, characterized in that: The carbonization process described in step 3 is carried out under an argon atmosphere with a gas flow rate of 50-500 sccm.
5. A two-dimensional ultrathin porous nitrogen-doped carbon composite material, characterized in that, It is prepared by the preparation method described in any one of claims 1-4.
6. The two-dimensional ultrathin porous nitrogen-doped carbon composite material according to claim 5, characterized in that: The two-dimensional ultrathin porous nitrogen-doped carbon composite material has a sheet-like porous structure and is loaded with metal single atoms and metal nanoparticles; wherein the metal is one of iron, cobalt, nickel, manganese, silver and copper.
7. The two-dimensional ultrathin porous nitrogen-doped carbon composite material according to claim 5, characterized in that: The two-dimensional ultrathin porous nitrogen-doped carbon composite material has a specific surface area of 100-1000 m² / g and an average pore size of 10-50 nm.
8. The application of a two-dimensional ultrathin porous nitrogen-doped carbon composite material according to any one of claims 5-7 in electromagnetic wave absorption, electromagnetic shielding, electromagnetic compatibility, medical radiation protection or radar stealth materials.
Citation Information
Cited By
Preparation method and application of multifunctional two-dimensional diatomic nano-enzyme material
CN121775894A